Bladder Smooth Muscle Cells Differentiation from Dental Pulp Stem Cells: Future Potential for Bladder Tissue Engineering - Bing Song; Wenkai Jiang; Amr Alraies; Qian Liu; Vijay Gudla; Julia Oni; Xiaoqing Wei; Alastair Sloan; Longxing Ni; Meena Agarwal (Hindawi Limited, 2016)
Dental pulp stem cells (DPSCs) are multipotent cells capable of differentiating into multiple cell lines, thus providing an alternative source of cell for tissue engineering. Smooth muscle cell (SMC) regeneration is a crucial step in tissue engineering of the urinary bladder. It is known that DPSCs have the potential to differentiate into a smooth muscle phenotype in vitro with differentiation agents. However, most of these studies are focused on the vascular SMCs. The optimal approaches to induce human DPSCs to differentiate into bladder SMCs are still under investigation. We demonstrate in this study the ability of human DPSCs to differentiate into bladder SMCs in a growth environment containing bladder SMCs-conditioned medium with the addition of the transforming growth factor beta 1 (TGF-β1). After 14 days of exposure to this medium, the gene and protein expression of SMC-specific marker (α-SMA, desmin, and calponin) increased over time. In particular, myosin was present in differentiated cells after 11 days of induction, which indicated that the cells differentiated into the mature SMCs. These data suggested that human DPSCs could be used as an alternative and less invasive source of stem cells for smooth muscle regeneration, a technology that has applications for bladder tissue engineering.